Effect of genetic specifics of patients on myocardial contractility after acute myocardial infarction: a literature review - S. E. Golovenkin; S. Yu. Nikulina; M. G. Bubnova; V. N. Maksimov (Российский кардиологический журнал, 2022)
In this literature review, we analyzed studies on the influence of genetic specifics of patients on the restoration of myocardial contractility after acute myocardial infarction. Data on the influence of genetic characteristics on the myocardial repair, remodeling process, and the restoration of cardiac contractility are presented. The use of genetic methods in the examination of patients and further consideration of individual characteristics when prescribing therapy will make it possible to implement a personalized approach to each patient. This will improve the effectiveness of treatment and the disease prognosis.